[18F]Fluorodeoxyglucose PET for Interventional Oncology in Liver Malignancy - Samim, Morsal; El-Haddad, Ghassan E; Molenaar, Izaak Quintes; Prevoo, Warner; van den Bosch, Maurice A A J; Alavi, Abass; Lam, Marnix G E H (PET clinics, 2014)
[(18)F]Fluorodeoxyglucose (FDG) PET is a functional imaging tool that provides metabolic information, which has the potential to detect a lesion before it becomes anatomically apparent. This ability constitutes a strong argument for using FDG-PET/computed tomography (CT) in the management of oncology patients. Many studies have investigated the accuracy of FDG-PET or FDG-PET/CT for these purposes, but with small sample sizes based on retrospective cohorts. This article provides an overview of the role of FDG-PET or FDG-PET/CT in patients with liver malignancies treated by means of surgical resection, ablative therapy, chemoembolization, radioembolization, and brachytherapy, all being liver-directed oncologic interventions.